2002
DOI: 10.1016/s0736-0266(02)00022-0
|View full text |Cite
|
Sign up to set email alerts
|

Chondropathy after meniscal tear or partial meniscectomy in a canine model

Abstract: A primary goal in considering treatment for meniscal injuries is the preservation of the health of the articular cartilage. However, the chondroprotective effects of various techniques for meniscal injury treatments are unknown. We used a canine model to quantify articular cartilage degeneration in the medial compartment of the canine knee, resulting from a surgically created tear or a partial meniscectomy (PM) of the posterior region of the medial meniscus (each group, n = 10). After sacrifice at 12 weeks, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
68
0
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 77 publications
(72 citation statements)
references
References 29 publications
3
68
0
1
Order By: Relevance
“…Injury or loss of meniscal tissue potentially leads to pain, knee dysfunction, and osteoarthritis at long term. [1][2][3] Healing of ruptured menisci is usually limited to the vascularized areas in the outer onethird of the meniscus. 4,5 Studies have demonstrated that healing of the knee is inversely related to the amount of meniscal tissue resected.…”
Section: Introduction Lmentioning
confidence: 99%
“…Injury or loss of meniscal tissue potentially leads to pain, knee dysfunction, and osteoarthritis at long term. [1][2][3] Healing of ruptured menisci is usually limited to the vascularized areas in the outer onethird of the meniscus. 4,5 Studies have demonstrated that healing of the knee is inversely related to the amount of meniscal tissue resected.…”
Section: Introduction Lmentioning
confidence: 99%
“…In addition to the pain and loss of function associated with a meniscal tear, damage and degenerative changes in the meniscus ultimately lead to loss of cartilage and development of OA [13,29,49,60], with 2 . 3 of patients having radiographic knee OA develop within 5 to 15 years [37].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the pain and loss of function associated with the initial meniscal injury, damage or loss of meniscal tissue is associated with degenerative changes in the joint that ultimately lead to osteoarthritis (OA) (12)(13)(14). Studies of an ovine model of meniscal repair have shown that unrepaired and failed repair of the meniscus leads to the development of tibiofemoral and patellofemoral OA within 6 months of a radial meniscal tear (15).…”
mentioning
confidence: 99%
“…Studies of an ovine model of meniscal repair have shown that unrepaired and failed repair of the meniscus leads to the development of tibiofemoral and patellofemoral OA within 6 months of a radial meniscal tear (15). In addition, both partial meniscectomy and partially healed meniscal incisions in a canine model were shown to result in significant increases in cartilage chondropathy and decreased cartilage tensile properties (12). Furthermore, studies in patients with symptomatic knee OA have revealed that both meniscal damage and malposition are associated with an increased risk of cartilage loss (16).…”
mentioning
confidence: 99%